Perceptions of Oral Health, Preventive Care, and Care‐Seeking Behaviors Among Rural Adolescents. (December 2014) - Dodd, Virginia J.; Logan, Henrietta; Brown, Cameron D.; Calderon, Angela; Catalanotto, Frank
ABSTRACT BACKGROUND An asymmetrical oral disease burden is endured by certain population subgroups, particularly children and adolescents. Reducing oral health disparities requires understanding multiple oral health perspectives, including those of adolescents. This qualitative study explores oral health perceptions and dental care behaviors among rural adolescents. METHODS Semistructured individual interviews with 100 rural, minority, low socioeconomic status adolescents revealed their current perceptions of oral health and dental care access. Respondents age ranged from 12 to 18 years. The sample was 80% black and 52% male. RESULTS Perceived threat from dental disease was low. Adolescents perceived regular brushing and flossing as superseding the need for preventive care. Esthetic reasons were most often cited as reasons to seek dental care. Difficulties accessing dental care include finances, transportation, fear, issues with Medicaid coverage and parental responsibility. In general, adolescents and their parents are in need of information regarding the importance of preventive dental care. CONCLUSIONS Findings illuminate barriers to dental care faced by low‐income rural adolescents and counter public perceptions of government‐sponsored dental care programs as being "free" or without cost. The importance of improved oral health knowledge, better access to care, and school‐based dental care is discussed.